Crowdsourcing for collaborative crisis communication: a systematic review - Pestana, Maria Clara; Ribeiro, Ailton; Vieira, Vaninha (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2024: Anais do XIX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2024.237802, 2024)
Efficient crisis response and support during emergency scenarios rely on collaborative communication channels. Effective communication between operational centers, civilian responders, and public institutions is vital. Crowdsourcing fosters communication and collaboration among a diverse public. The primary objective is to explore the state-of-the-art in crowdsourcing for collaborative crisis communication guided by a systematic literature review. The study selected 20 relevant papers published in the last decade. The findings highlight solutions to facilitate rapid emergency responses, promote seamless coordination between stakeholders and the general public, and ensure data credibility through a rigorous validation process.